Enhancing CO2 Electrocatalysis on 2D Porphyrin‐Based Metal–Organic Framework Nanosheets Coupled with Visible‐Light. Issue 2 (17th November 2020) - Zhou, Yue; Zheng, Lirong; Yang, Deren; Yang, Haozhou; Lu, Qichen; Zhang, Qinghua; Gu, Lin; Wang, Xun
Abstract: 2D catalysts combined with single atom sites are promising candidates to promote CO2 reduction performance, but the ability to target stable materials with distinct structure still remains challenging. Herein, a series of single metal atoms anchored 2D metal–organic framework nanosheets (MOF‐NS‐M) with visualized and well‐ordered mesoporous structures are fabricated and exhibit enhanced CO2 reduction activity and selectivity with the assistance of visible‐light. Encouragingly, the CO Faradaic efficiency of MOF‐NS‐Co exceeds 90% in a wide potential window of −0.5 to −1.0 V versus RHE and reaches 98.7% with 100 mV positive shift compared with the result measured under dark. The catalytic kinetics studies show a fast initial electron transfer to CO2 to form *COO −, thanks to the sufficient exposed active sites resulting from the nanosheet nature and adjusted electron transfer pathway caused by the porphyrin photoswitch. Abstract : A series of stable porphyrin‐based single site metal–organic framework (MOF) nanosheets with visualized and well‐ordered mesoporous structures are prepared. With the assistance of light‐fields, these catalysts exhibit enhanced intrinsic activity and energy efficiency for CO2 electroreduction, thanks to the sufficient exposed active sites, excellent conductivity, and adjusted electron transfer pathway deriving from the nanosheet nature and porphyrin photoswitch.